Recommendations for promoting the engagement of older people in activities to prevent falls. Issue 3 (1st June 2007) - Yardley, L; Beyer, N; Hauer, K; McKee, K; Ballinger, C; Todd, C
Abstract : Objective: To develop recommendations for promoting uptake of and adherence to falls-prevention interventions among older people. Design: The recommendations were initially developed from literature review, clinical experience of the core group members, and substantial qualitative and quantitative studies of older people's views. They were refined through a consultation process with members of the falls-prevention community, drawing on Delphi survey and nominal group techniques. Transparency was enhanced by recording and reporting aspects of the iterative consultation process such as the degree of consensus and critical comments on drafts of the recommendations. Setting: The recommendations were developed and refined at three meetings of the core group, and through internet-based consultation and two meetings involving members of the wider falls-prevention community. Participants: The authors developed the recommendations incorporating the feedback from the researchers and practitioners responding to a broad-based internet consultation and consulted in the meetings. Results: A high degree of consensus was achieved. Recommendations addressed the need for public education, ensuring that interventions were compatible with a positive identity, tailoring interventions to the specific situation and values of the individual, and using validated methods to maintain longer-term adherence. Conclusion: These recommendations represent a consensus based on current knowledge and evidence, but the evidence base from which these recommendations were developed was limited, and not always specific to prevention of falls. To increase the effectiveness of falls-prevention interventions, further research is needed to identify the features of falls-prevention programmes that will encourage older people's engagement in them.